Pengaruh Kepemimpinan dan Motivasi Kepala Sekolah terhadap Disiplin Kerja Guru di SD Negeri 243 Palembang : The Influence of Principal Leadership and Motivation on Teacher Work Discipline at Public Elementary School 243 Palembang - Reisa Bernia; Meilia Rosani; Nurlina Nurlina (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to examine the influence of principal leadership and motivation on teacher work discipline at Public Elementary School 243 Palembang. Teacher discipline is a crucial factor in improving the quality of education, as effective leadership and strong motivation are believed to foster more consistent work discipline. A quantitative approach with a survey method was employed, involving a total sample of 45 teachers selected through a total sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability (? = 0.89). Multiple linear regression was used for data analysis. The results revealed that principal leadership had a significant effect on teacher work discipline (? = 0.412; p = 0.003), while motivation from the principal also had a significant effect (? = 0.367; p = 0.008). Taken together, leadership and motivation significantly contributed to teacher discipline, with a coefficient of determination (R²) of 0.612. This indicates that 61.2% of the variation in teacher work discipline is explained by principal leadership and motivation, while the remaining 38.8% is influenced by other factors beyond the scope of this study. These findings suggest that participatory leadership combined with motivation strategies emphasizing rewards and coaching can substantially enhance teacher discipline. The study offers practical implications for elementary school management, particularly highlighting the importance of inspirational leadership and continuous motivation in fostering a sustainable culture of discipline within the school environment.